Urgensi Model Pembelajaran Interaktif dalam Meningkatkan Prestasi dan Motivasi Belajar Siswa dalam Mata Pelajaran Pendidikan Agama Islam - Hakim, Fauzi Rahmanul (Tsamratul Fikri | Jurnal Studi Islam, 2021)
In learning Islamic Religious Education (PAI) students need a learning model that is appropriate and precise in its characteristics. Learning model is termed by interpreting a broader scope than the learning method or strategy. Therefore, the learning model can be interpreted as planning which is used as a reference or rule in the learning process carried out in the classroom and can be a determinant of learning equipment such as teaching materials, books, curriculum, and so on. So it can be said that the learning model is a directional framework from the educator for the teaching process. This research tries to present an overview of the learning problems of an interactive model in the practice of Islamic education. Islamic education is now faced with various kinds of challenges, demands and needs that have never existed before. So it is not enough with just one learning model, it takes innovation in the renewal of the learning model that is tailored to the system needs, curriculum, human resource competencies, infrastructure, and others. If not, then Islamic education in practice will be increasingly left behind because it becomes a problem of learning models that do not adapt to developments. This research uses a literature study approach, data collection through text studies, then the data obtained is analyzed using content analysis. This method intends to analyze the problems of interactive learning in Islamic education practices. So it becomes a solution if the urgency learning model is made into a good innovation from its weaknesses and strengths. Because the learning process of students will be considered more effective if students after learning can find out something that was not previously known. So, learning achievement will change for the better with a change in new behavior in the level of reason, knowledge, thinking or advancement of physical potential.